Enabling B2B Customer Performance Through AI Assimilation: The Mediating Role of Customer Experience in Indonesian Markets - Ary Rahmansyah; Kurniawati; Renny Risqiani (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the influence of AI adoption, social value, informational value, and ease of use on customer experience and their effects on customer performance within the B2B sector in Indonesia. A quantitative methodology was utilized using a Likert-scale questionnaire administered to B2B companies implementing AI, and the data were examined using Structural Equation Modeling (SEM) with AMOS 22. The findings demonstrate that AI adoption, informative value, and usability positively influence consumer experience, whereas dependence obstacles exert a negative impact. Conversely, social value, enjoyment obstacles, and performance barriers exhibit no substantial impact. Moreover, customer experience significantly enhances customer performance. The findings indicate that in the B2B setting, companies emphasize the functional advantages of AI, like information quality and service convenience, over social value or perceived technological obstacles. This study suggests that the degree of AI integration, the quality of value experienced by consumers, and the firm's capacity to control reliance on technology partners are critical elements in optimizing the efficacy of AI in enhancing customer performance.